Blow-up result in a Cauchy problem for the nonlinear viscoelastic Petrovsky equation - PiÅŸkin, Erhan (International Journal of Advanced Mathematical Sciences, 2014)
In this paper, we consider a Cauchy problem for the nonlinear viscoelastic Petrovsky equation. We obtain the blow up of solutions by applying a lemma due to Zhou.